Exploring Love, Loyalty, and Betrayal in "The Remains of the Day" by Kazuo Ishiguro (International Journal of Food and Nutritional Sciences, 2022)
This research paper, explore into the intricate themes of love, loyalty, and betrayal within the context of Kazuo Ishiguro's "The Remains of the Day." The novel is set post-World War II and follows Stevens, an English butler, as he reflects on his unwavering commitment to his former employer, Lord Darlington. The paper provides an in-depth analysis of Stevens' struggles with repressed feelings for Miss Kenton, a fellow staff member. This text argues that Stevens' unwavering adherence to duty and loyalty often leads him astray from forming meaningful relationships.Using textual evidence from Ishiguro's writing, this paper demonstrates the emotional consequences of unquestioning loyalty and its correlation to perceived betrayal. It further highlights how these themes are intricately connected with the broader socio-historical context of the novel. Paper analyzes the effect of servitude on characters' personal lives and the moral dilemmas encountered due to their dedication to those they serve.